Dicyanovinyl-substituted oligothiophenes: Structure-property relationships and application in vacuum-processed small molecule organic solar cells - Fitzner, R; Reinold, E; Mishra, A; Mena-Osteritz, E; Bäuerle, P; Ziehlke, H; Körner, C; Leo, K; Riede, M; Weil, M; Tsaryova, O; Weiß, A; et al. (Wiley, 2011)
Efficient synthesis of a series of terminally dicyanovinyl (DCV)-substituted oligothiophenes, DCVnT 1-6, without solubilizing side chains synthesized via a novel convergent approach and their application as electron donors in vacuum-processed m-i-p-type planar and p-i-n-type bulk heterojunction organic solar cells is described. Purification of the products via gradient sublimation yields thermally highly stable organic semiconducting materials in single crystalline quality which allows for X-ray structure analysis. Important insights into the packing features and intermolecular interactions of these promising solar cell materials are provided. Optical absorption spectra and electrochemical properties of the oligomers are investigated and valuable structure-property relationships deduced. Photovoltaic devices incorporating DCVnTs 4-6 showed power conversion efficiencies up to 2.8% for planar and 5.2% for bulk heterojunction organic solar cells under full sun illumination (mismatch corrected simulated AM 1.5G sunlight). The 5.2% efficiency shown here represents one of the highest values ever reported for organic vacuum-deposited single heterojunction solar cells. © 2011 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.